Універсальні фільтруючі системи як ефективний спосіб підвищення якості металопродукції - Смірнов, О.М.; Немсадзе, Г.Г.; Джоджуа, Р.А.; Шарандін, К.М.; Рябий, Д.В. (Physico-technological Institute of Metals and Alloys, 2023)
In the given article the developed universal filtering system (UFS) is resulted, allowing to carry out effectively metal refining in an intermediate ladle of the continuous casting machine (CCM) during casting. This system was developed on the basis of deep theoretical analysis, physical modeling and industrial research. A number of laboratory tests with the use of models were carried out. Physical modeling allowed to determine the optimal design parameters of the filtering system elements, as well as the choice of their optimal quantity and location in the volume of the intermediate ladle, which allows to achieve the highest efficiency of removal of non-metallic inclusions and to ensure stable and safe operation of the intermediate ladle during casting of the metal series at CCM. As a result of theoretical, laboratory and industrial researches it is shown that blowing of a liquid bath of metal in an industrial ladle with argon provides refining effect in part of removal of large non-metallic inclusions. The greatest effect can be achieved with the use of bubble beams (blocks), providing bubble blowing. The results of industrial research at one of the metallurgical enterprises with converter steel production, which includes several slab CCMs, are presented. In industrial conditions it is established that the number of large single non-metallic inclusions is lower than in comparative slabs (without blowing) when blowing steel with argon in the tundish. The developed system "UFS" allows to reduce the range of the general index of metal contamination by non-metallic inclusions due to the complex approach to metal refining in the intermediate ladle. It should be noted, that this system has increased versatility and the experience can be used at the other enterprises of the industry, regardless of the type of CCM and design features of the intermediate ladle.